Effect of Dietary Methylsulfonylmethane Supplementation on Growth Performance, Hair Quality, Fecal Microbiota, and Metabolome in Ragdoll Kittens - Guo, Dan; Zhang, Limeng; Zhang, Lingna; Han, Sufang; Yang, Kang; Lin, Xinye; Wen, Chaoyu; Tong, Aorigeile; Zhang, Meiyu; Yin, Yulong; Deng, Baichuan (Frontiers in Microbiology, 2022)
Methylsulfonylmethane (MSM) is a natural sulfur-containing organic substance that has many biological functions, such as antioxidant, anti-inflammatory, skin nourishing, and hair growth-promoting effects. This study was conducted to determine the effect of MSM supplementation on growth performance, antioxidant capacity, and hair quality in kittens. A total of 21 Ragdoll kittens were assigned to three diets by initial body weight and gender: basal diet supplemented with 0%, 0.2%, and 0.4% MSM (CON, LMSM, and HMSM groups) for 65 days. During the whole period, the food intake of kittens in the MSM-treated groups tended to be higher (P < 0.10) compared with the CON group, and the average daily gain (ADG) had no significant difference when compared to the kittens in the CON group (P > 0.05). Antioxidant capacity had no significant difference (P > 0.05) among the groups. The scale thickness of hair tended to be smaller in the LMSM group compared to the CON group (P < 0.10) and decreased significantly (P < 0.05) over time from d 0 to d 65 in the LMSM group, indicating the improvement of hair quality. Besides, supplementation with LMSM increased bacterial diversity. Kittens fed MSM had no significant differences in fecal genus at the end of the study. No significant differences in fecal short-chain fatty acids were observed among groups. Fecal metabolomics analysis further revealed that MSM hardly affected the metabolites. Overall, dietary supplementation with 0.2% MSM can improve the hair quality of kittens. Furthermore, 0.2∼0.4% of MSM had no detrimental effects on serum biochemistry, growth performance, gut microbiota, and metabolome, which supports the safety inclusion of MSM to a certain degree in feline diets. To the best of our knowledge, this is the first study to investigate the effects of MSM supplementation in cats.